Penta Helix : Lima Variabel Unsur Kekuatan Dalam Pengembangan Desa Wisata Taman Langit, Kecamatan Batu Layar, Kabupaten Lombok Barat - Aji, Wahyu Trisno (Empowerment: Jurnal Pengabdian pada Masyarakat, 2023)
This research discusses the application of the penta helix model in the development of the Taman Langit tourist village in Bengkuang Hill, Bengkaung village, Gunungsari sub-district, West Lombok district, NTB. The penta helix model emphasizes the important role of five main actors, namely government, community, business people, media and academics, in building and developing tourism destinations. Harmonious collaboration between these five factors is considered very crucial for the smooth development of village tourism. In the context of the Taman Langit tourist village, the government has a role as a provider of tourism access and infrastructure, while the community and business people act as the main actors who run and develop village tourism. The media functions as a promotional tool, while historians provide direction, consultation and predictions regarding the development of village tourism. Through the penta helix approach, it is hoped that people from various sectors can enjoy the positive benefits resulting from the development of the Taman Langit tourist village. This research uses a type of library study (library research) with secondary data in the form of literature such as books, journals, magazines and websites that are relevant to the research. Key words: penta helix, sky garden, tourism